The Effect of Social Emotional Learning on Elementary School Students' Social Skills: A Quantitative Approach - Maria Ulfah; Supriadi; Andika Arisetyawan (MANDAILING GLOBAL EDUKASIA, 2026)
Developing robust social skills in early childhood is foundational to academic success and lifelong emotional well-being. Despite its importance, conventional elementary curricula predominantly focus on cognitive metrics, often leaving teachers unequipped to address rising behavioral challenges and social deficits in the modern classroom. This study aims to examine the effect of Social Emotional Learning (SEL) on the social skills of elementary school students. Employing a quantitative quasi-experimental framework, this study involved 67 fifth-grade students, assigned to an experimental class (n = 32, receiving SEL intervention) and a control class (n = 35, receiving conventional instruction). Data on students' social skills were systematically gathered using a validated questionnaire and analyzed through descriptive metrics alongside paired and independent sample t-tests. The empirical findings indicate that SEL implementation exerts a profoundly positive and statistically significant effect on students' social skills. The experimental group demonstrated an exponential increase in mean social skill scores, rising from a pre-treatment baseline of 65.07 (low category) to an impressive 94.28 (very high category) post-treatment. Conversely, the control group’s post-test mean stagnated at 63.19 (low category), establishing the definitive superiority of the SEL framework over traditional teaching methods (p < 0.05). Consequently, SEL serves as a potent and scalable pedagogical alternative to address contemporary deficits in elementary students' social skills. These results provide vital empirical backing for educational policymakers to systematically integrate emotional intelligence and social-framework modeling into primary school curricula.